Inhibition of insulin-like growth factors increases production of CXCL9/10 by macrophages and fibroblasts and facilitates CD8+ cytotoxic T cell recruitment to pancreatic tumours - Freeman, Patrick; Bellomo, Gaia; Ireland, Lucy; Abudula, Maidinaimu; Luckett, Teifion; Oberst, Michael; Stafferton, Ruth; Ghaneh, Paula; Halloran, Chris; Schmid, Michael C.; Mielgo, Ainhoa (Frontiers in Immunology, 2024)
Pancreatic ductal adenocarcinoma (PDAC) is a highly lethal malignancy with an urgent unmet clinical need for new therapies. Using a combination of in vitro assays and in vivo preclinical models we demonstrate that therapeutic inhibition of the IGF signalling axis promotes the accumulation of CD8+ cytotoxic T cells within the tumour microenvironment of PDAC tumours. Mechanistically, we show that IGF blockade promotes macrophage and fibroblast production of the chemokines CXCL9 and CXCL10 to facilitate CD8+ T cell recruitment and trafficking towards the PDAC tumour. Exploring this pathway further, we show that IGF inhibition leads to increased STAT1 transcriptional activity, correlating with a downregulation of the AKT/STAT3 signalling axis, in turn promoting Cxcl9 and Cxcl10 gene transcription. Using patient derived tumour explants, we also demonstrate that our findings translate into the human setting. PDAC tumours are frequently described as “immunologically cold”, therefore bolstering CD8+ T cell recruitment to PDAC tumours through IGF inhibition may serve to improve the efficacy of immune checkpoint inhibitors which rely on the presence of CD8+ T cells in tumours.